(untitled) (Global Journal of Science Frontier Research, 2020)
Anovel reagent for the dehydrogenation of cyclohexanone has been reported. Cyclohexanone was made to react with a novel reagent -KIO 3 as oxidizing agent in presence of acetic acid. The dehydrogenated compound was confirmed by comparison with the known compound. This metal free process is less time consuming and the easy availability and its stability makes it a versatile novel reagent for the dehydrogenation of cyclohexanone.